El paradigma de la Inteligencia Artificial al servicio del talento y la equidad - Ariza Gómez, Jesús
The observations made from research at the University of Cambridge are taken as a starting point to refute their appreciation of the negative nature that the development of AI can have as an applicable technology for talent management in personnel selection. The experiments carried out apparently focused from the field of behavior analysis and facial patterns, leaving little explanation about the incidence of competencies and their importance in selection processes. It is then argued, on the needs of organizations, the characterization of charges and roles by competencies and the relevance of emerging technologies such as AI to optimize management processes in business strategies, taking into account accepted theories both in the management of talent as in the technological field and visualizing the need for this emerging technology to provide solutions to needs, punctually observed in organizations, for their recruitment, selection and incorporation processes, among others related to the talent area. In the same perspective, a reflective point of view is offered on the incidence of human perceptions (social biases) on job opportunities and scaling of organizations, on their competitiveness and differentiation in a new normality.